A multidomain intervention against cognitive decline in an at-risk-population in Germany: Results from the cluster-randomized AgeWell.de trial. - Zülke AE; Pabst A; Luppa M; Roehr S; Seidling H; Oey A; Cardona MI; Blotenberg I; Bauer A; Weise S; Zöllinger I; Sanftenberg L; et al. (John Wiley and Sons, Inc., 2024)
INTRODUCTION: We investigated the effectiveness of a multidomain intervention to preserve cognitive function in older adults at risk for dementia in Germany in a cluster-randomized trial. METHODS: Individuals with a Cardiovascular Risk Factors, Aging, and Dementia (CAIDE) risk score ≥ 9 aged 60 to 77 years were recruited. After randomization of their general practitioner (GP), patients received a multidomain intervention (including optimization of nutrition and medication, and physical, social, and cognitive activity) or general health advice and GP treatment as usual over 24 months. Primary outcome was global cognitive performance (composite z score, based on domain-specific neuropsychological tests). RESULTS: Of 1030 participants at baseline, n = 819 completed the 24-month follow-up assessment. No differences regarding global cognitive performance (average marginal effect = 0.010, 95% confidence interval: -0.113, 0.133) were found between groups at follow-up. Perceived restrictions in intervention conduct by the COVID-19 pandemic did not impact intervention effectiveness. DISCUSSION: The intervention did not improve global cognitive performance. HIGHLIGHTS: Overall, no intervention effects on global cognitive performance were detected. The multidomain intervention improved health-related quality of life in the total sample. In women, the multidomain intervention reduced depressive symptoms. The intervention was completed during the COVID-19 pandemic.
Keywords: cognitive function; dementia; lifestyle; prevention; randomized controlled trial; Aged; Female; Humans; Cognitive Dysfunction; COVID-19; Dementia; Pandemics; Quality of Life; Risk Factors